2013
DOI: 10.1002/embr.201338041
|View full text |Cite
|
Sign up to set email alerts
|

Obesity resistance and deregulation of lipogenesis in Δ6‐fatty acid desaturase ( FADS 2) deficiency

Abstract: D-6-fatty acid desaturase (FADS2) is the key enzyme in the biosynthesis of polyunsaturated fatty acids (PUFAs), the essential structural determinants of mammalian membrane lipid-bilayers. We developed the auxotrophic fads2 À/À mouse mutant to assess the enigmatic role of x3-and x6-PUFAs in lipid homeostasis, membrane structure and function. Obesity resistance is another major phenotype of the fads2 À/À mutant, the molecular basis of which is unknown. Phospholipidomic profiling of membrane systems of fads2 À/À … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 20 publications
5
56
0
Order By: Relevance
“…The current study validated the use of 3T3‐L1 adipocytes for studying diet regulation of the FADS enzymes and further showed that adipocyte FA content is influenced by the FADS pathway. Continuing this line of investigation is relevant given that the FADS enzymes are expressed in human adipose tissue and recent research in a Fads2‐/‐ mouse suggests a role for desaturases in the development of obesity‐related complications . Future investigations whereby desaturase expression is altered (i.e., over‐expressed or inhibited) in 3T3‐L1 cells will generate new insights regarding the role of these enzymes as mediators of PUFA content and bioactivity in adipocytes.…”
Section: Discussionmentioning
confidence: 97%
“…The current study validated the use of 3T3‐L1 adipocytes for studying diet regulation of the FADS enzymes and further showed that adipocyte FA content is influenced by the FADS pathway. Continuing this line of investigation is relevant given that the FADS enzymes are expressed in human adipose tissue and recent research in a Fads2‐/‐ mouse suggests a role for desaturases in the development of obesity‐related complications . Future investigations whereby desaturase expression is altered (i.e., over‐expressed or inhibited) in 3T3‐L1 cells will generate new insights regarding the role of these enzymes as mediators of PUFA content and bioactivity in adipocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, when cells lack a significant Δ6‐desaturase activity, such as K562, the synthesis of Scia is favored over its 20:3 isomer . Thus a fads2 −/− mouse mutant accumulates Scia in phospholipids by replacing, in part, arachidonic acid and other PUFA . The physiological effects of Scia were consequently attributed to this arachidonate substitution.…”
Section: Discussionmentioning
confidence: 99%
“…In such studies, D6D has received much more attention compared to D5D, with respect to metabolic disorders, because data demonstrated strong positive correlations between increased D6D activity and insulin resistance, BMI, and T2DM, while D5D activities showed negative correlation [15, 3236]. Additionally, metabolic benefits of D6D inhibition were also predicted from the results that D6D KO mice exhibited resistance against HFD-induced obesity [37]. …”
Section: Discussionmentioning
confidence: 99%